Improved vigilance after sodium oxybate treatment in narcolepsy: a comparison between in‐field and in‐laboratory measurements. (23rd February 2016) - van Schie, Mojca K. M.; Werth, Esther; Lammers, Gert Jan; Overeem, Sebastiaan; Baumann, Christian R.; Fronczek, Rolf
Summary: This two‐centre observational study of vigilance measurements assessed the feasibility of vigilance measurements on multiple days using the Sustained Attention to Response Task and the Psychomotor Vigilance Test with portable task equipment, and subsequently assessed the effect of sodium oxybate treatment on vigilance in patients with narcolepsy. Twenty‐six patients with narcolepsy and 15 healthy controls were included. The study comprised two in‐laboratory days for the Maintenance of Wakefulness Test and the Oxford Sleep Resistance test, followed by 7‐day portable vigilance battery measurements. This procedure was repeated for patients with narcolepsy after at least 3 months of stable treatment with sodium oxybate. Patients with narcolepsy had a higher Sustained Attention to Response Task error count, lower Psychomotor Vigilance Test reciprocal reaction time, higher Oxford Sleep Resistance test omission error count adjusted for test duration (Oxford Sleep Resistance testOMIS / MIN ), and lower Oxford Sleep Resistance test and Maintenance of Wakefulness Test sleep latency compared with controls (all P  < 0.01). Treatment with sodium oxybate was associated with a longer Maintenance of Wakefulness Test sleep latency ( P  < 0.01), lower Oxford Sleep Resistance testOMIS / MIN ( P  = 0.01) and a lower Sustained Attention to Response Task error count ( P  =   0.01) in patients with narcolepsy, but not with absolute changes in Oxford Sleep Resistance test sleep latency or Psychomotor Vigilance Test reciprocal reaction time. It was concluded that portable measurements of sustained attention as well as in‐laboratory Oxford Sleep Resistance test and Maintenance of Wakefulness Test measurements revealed worse performance for narcoleptic patients compared with controls, and that sodium oxybate was associated with an improvement of sustained attention and a better resistance to sleep.